Healthy way of life - the main condition of teenager's deviant behaviour prevention (historical aspect) - Budagjans G.N (Kharkov National Pedagogical University, 2010)
In the article is examined the scientific approaches to the notions healthy way of life, deviant, groups of social risk, difficulty to be brought up, delinquency. The main components and elements of healthy way of life are revealed (rational work-rest cycle, healthy eating, physical activity, personal hygiene, absence of bad habits). The paramount importance of the arrangement of extracurricular and out-of-school work for healthy way of life formation for deviant teenagers is underlined.